Unusual Idiopathic Calcinosis Cutis Universalis in a Child - Alabaz, Derya (S. Karger AG, 2009)
Calcinosis cutis is an uncommon disorder characterized by the progressive deposition of crystals of calcium phosphate (hydroxyapatite) in the skin in various areas of the body. It is classified into four types according to etiology, namely as dystrophic if calcium and phosphorus levels are normal and tissue damage is present, as idiopathic if calcium and phosphorus levels are normal and no tissue damage is present, or as metastatic if there is hypercalcemia or hyperphosphatemia. Medical and surgical treatments are options to cure calcinosis cutis. Medical therapy is not very effective. Surgical excision has shown to be beneficial, as it can provide a symptomatic relief. However, since calcinosis cutis limits are not always well defined, a recurrence of the lesions may occur. We dealt with a very rare form of calcinosis cutis in a healthy 6-year-old girl. There was no evidence of connective tissue disorder or abnormal mineral metabolism. Hence, she was diagnosed as idiopathic calcinosis cutis and, although calcifications in idiopathic cutis are most commonly localized to one area, our patient unusually exhibited widespread calcific deposits. Although the existing lesions showed slow improvement, systemic pamidronate therapy was effective in preventing the occurrence of new lesions. Surgical excision proved to be an effective and successful treatment. This report aims to raise doctors’ awareness on the presentation, etiopathogenesis, and course of the relatively rare idiopathic calcinosis cutis.